2015
DOI: 10.1186/s12906-015-0549-z
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the antibacterial activity of selected Pakistani honeys against multi-drug resistant Salmonella typhi

Abstract: BackgroundThe development of resistance to conventional anti-typhoid drugs and the recent emergence of fluoroquinolone resistance have made it very difficult and expensive to treat typhoid fever. As the therapeutic strategies become even more limited, it is imperative to investigate non-conventional modalities. In this context, honey is a potential candidate for combating antimicrobial resistance because it contains a broad repertoire of antibacterial compounds which act synergistically at multiple sites, thus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 40 publications
1
26
0
Order By: Relevance
“…The variation existed not only between different floral honeys but also between honeys with the same floral origins (Tables 2 and 3 Tables 2 and 3). The reason for variation in the potency of antibacterial activity of honey sharing a floral origin could be due to climatic conditions, soil composition and geographical areas of honey collection [26]. Variation in the level of antibacterial activity of honeys between different floral honey sources and within the same flora source has been reported in other studies as well [40,41].…”
Section: Resultsmentioning
confidence: 76%
See 2 more Smart Citations
“…The variation existed not only between different floral honeys but also between honeys with the same floral origins (Tables 2 and 3 Tables 2 and 3). The reason for variation in the potency of antibacterial activity of honey sharing a floral origin could be due to climatic conditions, soil composition and geographical areas of honey collection [26]. Variation in the level of antibacterial activity of honeys between different floral honey sources and within the same flora source has been reported in other studies as well [40,41].…”
Section: Resultsmentioning
confidence: 76%
“…This result means that these honeys have high H 2 O 2 activity in comparison with that of Manuka honey. In some previous studies, Beri, Jarrah, Buckwheat and Ulmo honeys were identified as possessors of high H 2 O 2 − related antibacterial activity [26,35,48]. H 2 O 2 is an important contributor to the antibacterial activity of honey and is present in variable concentrations in .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The essential oil of M. pulegium has been proven effective against E. coli and L. monocytogenes by several authors (Mahboubi and Haghi, 2008;Marzouk et al, 2008). Honey was shown activity against several bacterial strains including E. coli and L. monocytogenes (Vorlova et al, 2005;Rodriguez et al, 2012;Hussain et al, 2015). Bacteriocin has already demonstrated potent antibacterial activity against L. monocytogenes (Khay et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, Hussein et al (2015) [20] evaluated the antibacterial activity of honey against gram positive and gram negative bacteria and they found that the most effective concentration was 40% or above.…”
Section: Al-hasanimentioning
confidence: 99%